Chilling effects : repression, conformity, and power in the digital age / Jonathon W. Penney. - Penney, Jonathon W. (Cambridge University Press, 2026)
In Chilling Effects, Jonathon W. Penney explores the increasing weaponization of surveillance, censorship, and new technology to repress and control us. With corporations, governments, and extremist actors using big data, cyber-mobs, AI, and other threats to limit our rights and freedoms, concerns about chilling effects - or how these activities deter us from exercising our rights - have become urgent. Penney draws on law, privacy, and social science to present a new conformity theory that highlights the dangers of chilling effects and their potential to erode democracy and enable a more illiberal future. He critiques conventional theories and provides a framework for predicting, explaining, and evaluating chilling effects in a range of contexts. Urgent and timely, Chilling Effects sheds light on the repressive and conforming effects of technology, state, and corporate power, and offers a roadmap of how to respond to their weaponization today and in the future.